Haurgeulis’ Village Head Communication Strategy to Improve Community Services - Gartina, Roro Gina; Tri Lestari, Martha (Mediator: Jurnal Komunikasi, 2024)
This research analyzes the leadership communication strategies implemented by the head of Haurgeulis Village in Indramayu Regency to enhance public services. The research adopts a qualitative approach using Robert K. Yin's single holistic case study method. Data were collected through in-depth interviews with key informants, including the village chief, government staff, experts, village officials, and local community members. These informants were selected due to their direct involvement in Haurgeulis Village, providing valuable insights into decision-making and experiences. The data, along with the interview results, were then analyzed to gain a deeper understanding. The findings reveal that the village chief adopted three key strategies to achieve these objectives. First, planning: replacing all village officials, conducting Monday apel (assemblies), and organizing seminars and workshops. Second, implementation: involving the community in joint activities to drive improvements through tarling, istighosah, dialogue via social media, and the e-desa application. Third, evaluation: ensuring layered monitoring, using complaint boxes, and facilitating online chats through social media to address the community’s needs. These strategies improved public services through initiatives such as one-stop services, Si Kiceup, Ruwat Pajak, and Naruak Pajak, empowering the community, fostering transparency, and ultimately enhancing public services.